The Role of Innovation for Knowledge Management to Predispose Business Performance of Micro, Small, and Medium Enterprise (MSME) in Semarang City during Covid-19 outbreak - Pijar Puan Bakaritantri; Putut - Haribowo; Fatchun - Hasyim (Admisi dan Bisnis, 2021)
The objective of this research is to analyze the role of innovation for knowledge management to influence the MSMEs performance in Semarang City during COVID-19. This research used a Structural Equation Modeling (SEM). The primary data used in this research is collected from questionnaire. The amounts of the respondents are 176 who are the workers of MSMEs in Semarang City. The analysis tools used in this study is SPSS 23 for instrument testing and AMOS 22 for model fit, outlier evaluation, SEM assumption, and hypothesis testing. The results of this study showed that knowledge management significantly and positively influences business performance directly, knowledge management significantly and positively influences innovation directly, innovation significantly and positively influences business performance directly, and knowledge management significantly and positively influences business performance indirectly through innovation.